(untitled) (Journal of Applied Learning and Teaching, 2024)
A virtual reality (VR) simulation-based intervention was compared to conventional pronunciation teaching in an experimental study. The experimental and control groups were assigned at random, with the experimental group using virtual reality to practice pronunciation and the control group using traditional classroom teaching. Pre-post-intervention assessments included pronunciation tests and subjective self-evaluations. T-tests/ANCOVA were used to compare experimental and control group pronunciation test results. The self-evaluation questionnaires’ qualitative data were evaluated thematically to determine students’ virtual reality simulation experiences. Virtual reality simulation-based education was expected to increase English as a Foreign Language (EFL) pronunciation abilities more than the control group. Students in the experimental group were predicted to be more engaged and satisfied with virtual reality simulations. This research adds to the literature on EFL pronunciation training. It suggests that virtual reality influences Jordanian EFL pedagogy and proposes using virtual reality simulations in pronunciation training to promote language acquisition.